New Insights Into Microbial Induced Calcium Carbonate Precipitation Using Saccharomyces cerevisiae - Li, Zhimin; Li, Tianxiao (Frontiers in Microbiology, 2022)
Saccharomyces cerevisiae plays an important role in the mineralization of many metal ions, but it is unclear whether this fungus is involved in the mineralization of calcium carbonate. In this study, S. cerevisiae was cultured under various conditions to explore its ability to perform microbially induced calcium carbonate precipitation (MICP). Organic acids, yeast extract, and low-carbon conditions were the factors influencing the biomineralization of calcium carbonate caused by S. cerevisiae, and biomolecules secreted by the fungus under different conditions could change the morphology, size, and crystal form of the biosynthesized mineral. In addition, transcriptome analysis showed that the oxidation of organic acids enhanced the respiration process of yeast. This implied that S. cerevisiae played a role in the formation of calcium carbonate through the mechanism of creating an alkaline environment by the respiratory metabolism of organic acids, which could provide sufficient dissolved inorganic carbon for calcium carbonate formation. These results provide new insights into the role of S. cerevisiae in biomineralization and extend the potential applications of this fungus in the future.